SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PEMBIMBING TUGAS AKHIR MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) - Firayati Firayati; Muh. Ihsan Sarita; Statiswaty Statiswaty (Informatics Engineering Department of Halu Oleo University, 2016)
Nowadays, decision making process in supervisor selection at Information Engineering course still involving manual process by considering the expertise of each lecturer in particular subject. Wherein selecting supervisor, the department works ineffective in supervisor selecting who appropriate with student final project theme. Because of that, decision support system that could assist user in selecting supervisor who appropriate with assigned criteria is needed. This issues can be resolved by applying WP method. The alternative options are employment status, functional position, skills, responsibility, quota and availability. Alternative options with the highest weight will become the recommendation to be selected as a supervisor. Based on the test and evaluation result, we can conclude that this system could assist in selecting the first and the second supervisor for student. Keywords— Supervisor, Decision Support System, Weighted Product